MODEL PENGEMBANGAN SUPERVISI AKADEMIK MELALUI E-VISIONARY BEBRASIS KOMUNIKASI INTERPERSONAL DI MADRASAH ALIYAH - Adi Amanatulloh, Sahrul; Bunyamin; Yuliejantiningsih , Yovitha (Universitas Negeri Medan, 2025)
Abstract: This study aims to develop an academic supervision model based on E-Visionary through an interpersonal communication approach to enhance the effectiveness of academic supervision at Madrasah Aliyah Nudia, Semarang City. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results show that the developed model is highly feasible and effective, with validation scores of 89% from material experts, 83% from media experts, and 87% from teacher responses. The evaluation stage indicates that the E-Visionary application is effective, practical, and of high quality in academic supervision. Teachers found it helpful due to its structured, efficient, and user-friendly system, which supports quick feedback and professional communication with supervisors. This model contributes to strengthening teacher professionalism and supports the national education digital transformation policy. Keyword: Academic Supervision, E-Visionary, Interpersonal Communication, Development Model, ADDIE Abstrak: Penelitian ini bertujuan mengembangkan model supervisi akademik berbasis E-Visionary melalui pendekatan komunikasi interpersonal untuk meningkatkan efektivitas supervisi akademik di Madrasah Aliyah Nudia. Pendekatan penelitian menggunakan Research and Development (R&D) dengan model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Hasil penelitian menunjukkan bahwa model yang dikembangkan dinyatakan sangat layak dan efektif, dengan validasi ahli materi sebesar 89%, ahli media 83%, dan respon guru 87%. Tahap evaluasi menunjukkan bahwa aplikasi E-Visionary efektif, praktis, dan berkualitas dalam supervisi akademik. Guru merasa terbantu karena sistemnya terstruktur, efisien, mudah digunakan, serta mendukung umpan balik cepat dan komunikasi profesional dengan supervisor. Model ini berkontribusi terhadap penguatan profesionalisme guru dan mendukung kebijakan transformasi digital pendidikan nasional. Kata Kunci: Supervisi Akademik, E-Visionary, Komunikasi Interpersonal, Model Pengembangan ADDIE